"It's Changed Everything": Voices of Veterans in the Veteran-Directed Home and Community Based Services Program. Issue 2 (17th February 2019) - Mahoney, Ellen K.; Milliken, Aimee; Mahoney, Kevin J.; Edwards-Orr, Merle; Willis, Danny G.
ABSTRACT: The purpose of this study was to understand the value and impact of the Veteran-Directed Home and Community Based Services program (VD-HCBS) on Veterans' lives in their own voices. Focus groups and individual interviews by telephone were conducted to elicit participant perspectives on what was most meaningful, and what difference VD-HCBS made in their lives. Transcripts were analyzed using content analysis. The sample included 21 Veterans, with a mean age of 66±14, enrolled in VD-HCBS an average of 20.8 months. All were at risk of institutional placement based on their level of disability. Five major categories captured the information provided by participants: What a Difference Choice Makes; I'm a Person!; It's a Home-Saver; Coming Back to Life; and Keeping Me Healthy & Safe. Participants described the program as life changing. This study is the first time that Veterans themselves have identified the ways in which VD-HCBS impacted their lives, uncovering the mechanisms underlying positive outcomes. These categories revealed new ways of understanding VD-HCBS as an innovative approach to meeting the person-centered needs of Veterans wishing to remain at home, while experiencing quality care and leading meaningful lives, areas identified as priorities for improving long term services and supports.